The Effect of DM in Patients on General Anesthesia (Zien Journal of Social Sciences and Humanities, 2022)
The current study was conducted with the aim of knowing the changes in blood sugar in people with diabetes after giving a dose of general anesthesia for the purpose of performing surgical operations to the auditors of Imam Al-Sadiq Hospital (peace be upon him) and Al-Kifl General Hospital in Babel Governorate for the period from 3/1/2022 to 1/3/2022 by 30 samples ranging in age from (25-50) years 2 ml of venous blood was withdrawn and placed in a Gel tube, then placed in a centrifuge to separate the serum for the purpose of conducting a glucose test. The results showed that the diabetes test is 100% positive for diabetic patients. The results also showed a significant increase (P